C / iron-based composite material based on poplar / willow catkin fibers and preparation method and application of C / iron-based composite material
By depositing and carbon-thermal reduction of divalent zinc salts and trivalent iron salts on poplar/cat fibers, a high-performance C/iron-based composite material was prepared, which solved the shortcomings of poplar/cat fibers in pollutant degradation in the prior art, and achieved efficient photofenton degradation and magnetic recovery.
Patent Information
- Application Number
- CN202411251226.9
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-09-07
- Publication Date
- 2025-03-18
AI Technical Summary
The prior art is difficult to effectively utilize poplar/cattle fiber for photofenton degradation of pollutants, and nano zero-valent iron is prone to oxidation and inactivation in applications.
By collecting and cleaning poplar/willet catkins, divalent zinc salt and trivalent iron salt were deposited on the surface of poplar/willet fibers, the C/iron-based composite was prepared by carbon-thermal reduction method, and calcined and tested under different conditions to improve its photofenton degradation performance.
The high-performance carbon-supported zero-valent iron Fenton catalyst of poplar/cat fiber is achieved. The degradation rate of the catalyst can reach more than 99% in 2 minutes-20 minutes, and it has the ability to recover and reuse magnetically.
Smart Images

Figure CN119633830A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of catalysts for treating water pollution, and in particular to a C / iron-based composite material based on poplar / willow catkin fibers, and a preparation method and application thereof. Background Art
[0002] Biomass carbon materials are produced from waste biomass in nature, such as agricultural waste, urban organic waste, etc., which are calcined under medium-high temperature and oxygen-restricted conditions to form a type of biomass-based carbon materials with many pores and high degree of aromatization. The raw materials of biomass carbon materials are very abundant and belong to renewable resources in nature. Because carbon materials such as activated carbon and mesoporous carbon have large specific surface area, high pore volume, good chemical inertness, excellent mechanical and thermal stability, and hydrophobic properties on the surface, they are often used as good carriers for loading materials. Among them, poplar / willow trees produce a large amount of poplar / willow catkins every year, which pose a threat to people's health in the air and even damage the human respiratory system. In addition, due to the presence of a thick wax layer on the surface of the fiber, it floats on the water surface for a long time, causing water pollution. However, poplar / willow catkins have a tubular structure, a large specific surface area, and a large number of hydroxyl groups on the molecular skeleton, which can be used as a template for carbon microtubes, and then can be used as a carbon skeleton material for treating adsorbents in heavy metal ion wastewater. In addition, zero-valent iron is a highly active metal in nature, with abundant content, large specific surface area and strong reduction performance. Iron-based catalytic materials basically do not need to consider the problem of secondary pollution, but nano zero-valent iron is easily oxidized and deactivated and easily agglomerated during application.
[0003] Therefore, it is necessary to provide a C / iron-based composite material based on poplar / willow catkin fibers and its preparation method and application to solve the above problems and improve its photo-Fenton degradation performance of pollutants. Summary of the invention
[0004] Based on the above, the purpose of the present invention is to provide a C / iron-based composite material based on poplar / willow catkins fibers, which improves its photo-Fenton degradation performance on the basis of realizing the recycling and reuse of agricultural waste poplar / willow catkins.
[0005] To achieve the above object, the present invention adopts the following technical solutions:
[0006] A method for preparing a C / iron-based composite material based on poplar / willow catkin fibers comprises the following steps:
[0007] Collect poplar / willow catkins, wash and dry them to obtain pure poplar / willow catkins;
[0008] Dissolving a divalent zinc salt and a trivalent iron salt in a solvent to obtain a mixed solution;
[0009] Put pure poplar / willow catkins into the mixed solution and stir, adjust the pH to alkaline, and obtain a suspension;
[0010] The suspension is washed, filtered, dried and calcined to obtain a C / iron-based composite material.
[0011] As a preferred embodiment of the preparation method of a C / iron-based composite material based on poplar / willow fibers, in the mixed solution, the concentration of the divalent zinc salt is 20 mmol / L-40 mmol / L, and the molar ratio of the divalent zinc salt to the trivalent iron salt is 1:(1-2); in the suspension, the concentration of pure poplar / willow fibers is 8 g / L-12 g / L 。
[0012] As a preferred embodiment of the method for preparing a C / iron-based composite material based on poplar / willow fibers, the divalent zinc salt includes zinc nitrate hexahydrate, the trivalent iron salt includes ferric nitrate nonahydrate, and the solvent includes anhydrous ethanol.
[0013] As a preferred solution of the preparation method of the C / iron-based composite material based on poplar / willow catkins fibers, the drying temperature of the poplar / willow catkins is 50-70°C.
[0014] As a preferred solution of the preparation method of a C / iron-based composite material based on poplar / willow catkin fibers, the pure poplar / willow catkins are put into the mixed liquid and stirred for 10-60 minutes.
[0015] As a preferred solution for the preparation method of a C / iron-based composite material based on poplar / willow catkin fibers, the pH is adjusted to alkaline, with a pH value of 9-10.
[0016] As a preferred solution for the preparation method of a C / iron-based composite material based on poplar / willow fibers, the drying temperature of the suspension is 50-80°C; the calcination temperature is 600-800°C, and an inert atmosphere is maintained during the calcination process, preferably argon.
[0017] A C / iron-based composite material based on poplar / willow catkin fibers is prepared by any of the preparation methods described above.
[0018] A photo-Fenton catalyst comprises a C / iron-based composite material.
[0019] A catalytic method for a photo-Fenton catalyst performs photo-Fenton degradation under the conditions of different iron-zinc doping amounts, different synthesis systems of alcohol phase or water phase, and different calcination methods of air or argon.
[0020] The C / iron-based composite material based on poplar / willow catkin fibers described in the present application, wherein the poplar / willow catkins can be replaced by willow catkins.
[0021] The beneficial effects of the present invention are:
[0022] The present invention provides a C / iron-based composite material based on poplar / willow fiber and a preparation method and application thereof. On the basis of realizing the recycling and reuse of agricultural waste poplar / willow, a high-performance carbon-loaded zero-valent iron Fenton catalyst is prepared by a carbon thermal reduction method, and an iron-zinc metal salt is deposited on the surface of the poplar / willow fiber, and calcined under the protection of an inert gas at 750°C to obtain a C / iron-based composite material. At the same time, the photo-Fenton degradation performance of the catalyst is tested under the conditions of different iron-zinc doping amounts, different synthesis systems of an alcohol phase or an aqueous phase, and different calcination methods of air or argon. It can be obtained that the degradation rate of the catalyst can reach more than 99% in 2min-20min, wherein, in an ethanol alkali system, when the concentration of the divalent zinc salt is 30mmol / L, the molar ratio of the divalent zinc salt to the trivalent iron salt is 1:1, and the degradation rate of the catalyst obtained by calcination in an argon atmosphere is the best, at pH=2, the catalyst input amount is 0.4g·L -1 When the H2O2 dosage is 36mM, it takes no more than 2 minutes to degrade 200mg·L -1 The degradation rate of Rhodamine B dye can reach over 99%.
[0023] The above preparation method not only converts poplar / willow catkin fibers into carbon fibers, but also uses carbon thermal reduction to reduce iron salts to nano zero-valent iron, and zinc salts play a role as a porogen for carbon materials, further increasing the specific surface area of carbon fiber materials. This method allows nano zero-valent iron to be evenly dispersed on the carbon fiber tube wall, achieving effective bonding between carbon and zero-valent iron, improving the transmission efficiency of electrons, greatly increasing the efficiency of photo-Fenton degradation of high-concentration dyes, and the prepared C / iron-based composite material has the ability to be magnetically recycled and reused because it carries iron-based components, making it easy to recycle and reuse. BRIEF DESCRIPTION OF THE DRAWINGS
[0024] In order to more clearly illustrate the technical solutions in the embodiments of the present invention, the following briefly introduces the drawings required for use in the description of the embodiments of the present invention. Obviously, the drawings described below are only some embodiments of the present invention. For ordinary technicians in this field, other drawings can be obtained based on the contents of the embodiments of the present invention and these drawings without paying any creative work.
[0025] Figure 1 is a photo of the C / iron-based composite material prepared by the present invention, wherein a is the original poplar fluff, b is the poplar fluff after washing, c is the modified material, and d is the calcined material;
[0026] Figure 2 The SEM images of poplar fluff and its high-temperature carbonization, where a and b are original poplar fluff, and c and d are C-1;
[0027] Figure 3is the SEM image of carbon fiber and carbon fiber loaded iron-zinc based composite material, where a, b, c are carbon fiber, d, e, f are carbon fiber loaded iron-zinc based composite material;
[0028] Figure 4 It is the Mapping diagram and EDS diagram of C / Fe / Zn-5;
[0029] Figure 5 is the XRD pattern of the C / iron-based composite material prepared by the present invention, wherein a is C-1, b is C / Zn, c is C / Fe, and d is C / Fe / Zn-5;
[0030] Figure 6 is the RhB standard curve graph;
[0031] Figure 7 The photo-Fenton degradation and kinetic curves of the C / iron-based composite material prepared at different zinc and iron doping amounts of the present invention are shown, wherein a is C-1, b is C-2, c is C / Fe, d is C / Zn, e is Fe / Zn, f is C / Fe / Zn-1, g is C / Fe / Zn-2, h is C / Fe / Zn-3, i is C / Fe / Zn-4, j is C / Fe / Zn-5, k is C / Fe / Zn-6, l is C / Fe / Zn-7, and m is C / Fe / Zn-8;
[0032] Figure 8 : is a performance diagram of photo-Fenton degradation of RhB by the C / iron-based composite material prepared by the present invention under different pH conditions: wherein a is pH=1, b is pH=2, and c is pH=3;
[0033] Fig. 9 The performance diagram of the photo-Fenton degradation of RhB by the C / iron-based composite material prepared by the present invention under different H2O2 dosages is shown in FIG. 1 , wherein a is H2O2=16 mM, b is H2O2=32 mM, and c is H2O2=48 mM;
[0034] Fig.10 The performance diagram of the C / iron-based composite material prepared by the present invention for photo-Fenton degradation of RhB under different amounts of catalyst: a is the catalyst = 0.3 g·L -1 , b is catalyst = 0.4 g·L -1 , c is catalyst = 0.5 g·L -1 ;
[0035] Fig.11 is a Fourier transform infrared spectrum (FT-IR) of the C / iron-based composite material prepared by the present invention, wherein a is poplar fluff, b is C-1, c is C / Zn, d is C / Fe, and e is C / Fe / Zn-5;
[0036] Fig.12It is a specific surface area and pore size analysis diagram of the C / iron-based composite material prepared by the present invention, A is a nitrogen adsorption and desorption curve, and B is a pore size distribution diagram, wherein a is poplar fluff, b is C-1, c is C / Zn, d is C / Fe, and e is C / Fe / Zn-5;
[0037] Fig.13 is the three-dimensional fluorescence spectrum of the C / iron-based composite material prepared by the present invention, wherein A is before adsorption, B is after adsorption, and C is after reaction;
[0038] Fig.14 This is a cyclic photo-Fenton degradation experimental diagram of the iron-based composite material prepared by the present invention;
[0039] Fig.15 This is an optical photograph of the magnetic properties test of the C / iron-based composite material prepared by the present invention;
[0040] Fig.16 This is the result of the free radical capture photo-Fenton degradation of RhB experiment, where a is isopropanol, b is triethanolamine, c is p-benzoquinone, and d is C / Fe / Zn-5. DETAILED DESCRIPTION
[0041] For ease of understanding of the present invention, the present invention will be described more fully below. The present invention can be implemented in many different forms and is not limited to the embodiments described herein. On the contrary, the purpose of providing these embodiments is to make the understanding of the disclosure of the present invention more thorough and comprehensive. Unless otherwise defined, all technical and scientific terms used in the present invention belong to the technical field of the present invention.
[0042] This embodiment provides a method for preparing a C / iron-based composite material based on poplar / willow catkin fibers, and the specific steps are as follows:
[0043] S100: collecting poplar / willow catkins, washing and drying them to obtain pure poplar / willow catkins;
[0044] Specifically, the washing process needs to be washed with deionized water three times or more, and the drying temperature is 50-70°C, specifically set to 50°C or 60°C or 70°C, preferably 60°C, which is determined according to actual conditions.
[0045] S200: dissolving zinc nitrate hexahydrate and ferric nitrate nonahydrate in a solvent to obtain a mixed solution;
[0046] Specifically, the divalent zinc salt includes zinc nitrate hexahydrate, the trivalent iron salt includes ferric nitrate nonahydrate, and the solvent includes anhydrous ethanol. In the mixed solution, the concentration of the divalent zinc salt is 20mmol / L-40mmol / L, and the molar ratio of zinc nitrate hexahydrate to ferric nitrate nonahydrate is 1:(1-2). Specifically, when the concentration of zinc nitrate hexahydrate is 20mmol / L or 30mmol / L or 40mmol / L, the concentration of zinc nitrate hexahydrate is preferably 30mmol / L, and the ratio of Zn(NO3)2:Fe(NO3)3 is preferably 1.5mmol or 1.5mmol, which is determined according to actual conditions.
[0047] S300: pure poplar / willow catkins are placed in the mixed solution and stirred, and the pH is adjusted to alkaline to obtain a suspension;
[0048] Specifically, in the suspension, the concentration of pure poplar / willow catkins is 8g / L-12g / L, the concentration of pure poplar / willow catkins can be set to 8g / L or 10g / L or 12g / L, preferably 10g / L, the pure poplar / willow catkins are placed in the mixed solution and stirred for 10-60min, the stirring time can be set to 10min or 30min or 60min, preferably 30min, which is determined according to actual conditions; wherein, the pH value of the solution is adjusted by adding 6mol / L NaOH solution, and the pH value is 9-10.
[0049] S400: washing, filtering, drying and calcining the suspension to obtain a C / iron-based composite material.
[0050] Specifically, the drying temperature is 50-80°C, and the drying temperature can be specifically set to 50°C, 60°C or 80°C, preferably 60°C, which is determined according to actual conditions; the calcination temperature is 600-800°C, and can be specifically set to 600°C, 750°C or 800°C, preferably 750°C. During the calcination process, an inert atmosphere is maintained, preferably argon, which is determined according to actual conditions.
[0051] The present invention will be further described below by means of specific examples.
[0052] Example 1
[0053] A method for preparing a C / iron-based composite material based on poplar fibers:
[0054] The poplar fluff was collected and crushed, washed three times with deionized water, and then dried in an oven at 60°C for 6 h to obtain the cleaned pure poplar fluff;
[0055] 50 mL of anhydrous ethanol was measured and poured into a 150 mL conical flask, 0.3 g of zinc nitrate hexahydrate and 0.4 g of ferric nitrate nonahydrate (the concentration of zinc nitrate hexahydrate was 30 mmol / L) were weighed and put into the conical flask, and the conical flask was placed on a magnetic stirrer and stirred for 30 min to obtain a uniform mixed solution containing zinc nitrate and ferric nitrate;
[0056] Weigh 0.5g of pure poplar fluff into a 150mL conical flask, and stir the mixture in the flask for 30 minutes. Then adjust the pH value of the solution to 9-10 with 6mol / L NaOH solution to obtain a brown suspension;
[0057] After washing and filtering the suspension, it was placed in an oven at 60°C for 12 hours, and the obtained brown fiber was calcined at 750°C in a tubular furnace and kept warm for 1 hour to generate a C / iron-based composite material. As shown in Table 1, in this embodiment, Zn(NO3)2 is 1 mmol, Fe(NO3)3 is 1 mmol, and the prepared C / iron-based composite material is named C / Fe / Zn-3.
[0058] Figure 1 This is a photo of the material during the preparation of the C / Fe-based composite material. Figure 1 As shown, the poplar fluff fiber is milky white, and the fiber turns brown after the deposition of iron-zinc salts, proving that iron-zinc substances are deposited on the surface of the poplar fluff fiber. After carbonization, the sample is black, indicating that the poplar fluff is successfully carbonized. It can also be observed that it still presents a soft floc-like fiber state. It is preliminarily judged that the high temperature treatment does not destroy its fiber tube structure.
[0059] Example 2
[0060] The preparation method and reaction conditions are consistent with those of Example 1, with the addition of 50 mL of anhydrous ethanol and 0.5 g of pure poplar fluff, wherein the amount of Zn(NO3)2 is 1 mmol, the amount of Fe(NO3)3 is 2 mmol, the concentration of Zn(NO3)2 is 20 mmol / L, and the C / iron-based composite material prepared in this example is named C / Fe / Zn-4.
[0061] Example 3
[0062] The preparation method and reaction conditions are consistent with those of Example 1, with the addition of 50 mL of anhydrous ethanol and 0.5 g of pure poplar fluff, wherein the amount of Zn(NO3)2 is 1.5 mmol, the amount of Fe(NO3)3 is 1.5 mmol, and the concentration of Zn(NO3)2 is 30 mmol / L. The C / iron-based composite material prepared in this example is named C / Fe / Zn-5.
[0063] Example 4
[0064] The preparation method and reaction conditions are consistent with those of Example 1, with the addition of 50 mL of anhydrous ethanol and 0.5 g of pure poplar fluff, wherein the amount of Zn(NO3)2 is 1.5 mmol, the amount of Fe(NO3)3 is 3 mmol, and the concentration of Zn(NO3)2 is 30 mmol / L. The C / iron-based composite material prepared in this example is named C / Fe / Zn-6.
[0065] Example 5
[0066] The preparation method and reaction conditions are consistent with those of Example 1, with the addition of 50 mL of anhydrous ethanol and 0.5 g of pure poplar fluff, wherein the amount of Zn(NO3)2 is 2 mmol, the amount of Fe(NO3)3 is 2 mmol, and the concentration of Zn(NO3)2 is 40 mmol / L. The C / iron-based composite material prepared in this example is named C / Fe / Zn-7.
[0067] Example 6
[0068] The preparation method and reaction conditions are consistent with those of Example 1, with the addition of 50 mL of anhydrous ethanol and 0.5 g of pure catkins, wherein the amount of Zn(NO3)2 is 1 mmol, the amount of Fe(NO3)3 is 1 mmol, the concentration of Zn(NO3)2 is 20 mmol / L, and the C / iron-based composite material prepared in this example is named C / Fe / Zn-9.
[0069] In order to further illustrate the excellence of the present application, comparative examples 1-7 are added for illustration, as shown in Table 1, based on the addition of 50 mL of anhydrous ethanol and 0.5 g of pure poplar fluff, the other preparation methods and reaction conditions are consistent with those of Example 1.
[0070] Comparative Example 1 is C-1, in which Zn(NO3)2, Fe(NO3)3 and NaOH solution are not added;
[0071] Comparative Example 2 is C-2, in which Zn(NO3)2 and Fe(NO3)3 are not added;
[0072] Comparative Example 3 is C / Fe, wherein (Fe(NO3)3 is 2mmol;
[0073] Comparative Example 4 is C / Zn, wherein Zn(NO3)2 is 1 mmol;
[0074] Comparative Example 5 is C / Fe / Zn-1, wherein Zn(NO3)2 is 0.5mmol and Fe(NO3)3 is 0.5mmol;
[0075] Comparative Example 6 is C / Fe / Zn-2, wherein Zn(NO3)2 is 0.5mmol and Fe(NO3)3 is 1mmol;
[0076] Comparative Example 7 is C / Fe / Zn-8, wherein Zn(NO3)2 is 1 mmol, Fe(NO3)3 is 2 mmol, and no NaOH solution is added.
[0077] Table 1 Preparation formula of C / Fe-based composites with different Zn-Fe doping amounts
[0078]
[0079]
[0080] The morphology of the C / iron-based composite materials prepared in the above examples and comparative examples was observed using a scanning electron microscope.
[0081] like Figure 2 As shown in the figure, it is a SEM image of poplar fluff and its high-temperature carbonization. In the two cases a and b in the figure, it can be seen that the poplar fluff fiber has a hollow tubular structure. The fiber can be as long as several hundred millimeters, with a diameter of about 16μm. The poplar fluff has a large tubular cavity and a tube wall thickness of about 1.5μm. The two cases c and d in the figure are carbon tubes after high-temperature carbonization. From the figure c, it can be seen that it still has a good tubular structure after high-temperature treatment, and its carbon fiber length is significantly shortened by about 50μm. This is because the poplar fluff fiber is crushed and cleaned before carbonization. From the figure d, it can also be clearly observed that the diameter of its carbon fiber is about 10μm, which shows that the fiber has shrunk after high-temperature carbonization, and the tube wall has also become significantly thinner. The figure c clearly shows that the tube wall thickness of the carbon fiber has been reduced to about 400nm.
[0082] Figure 3 It is a high-magnification SEM image of carbon fiber, which clearly shows the surface structure of carbon fiber. It can be seen that the surface of carbon fiber is smooth, clean and free of impurities. In the figure, d, e, and f are carbon fiber-loaded iron-zinc-based composite materials. Compared with smooth carbon fiber, it still maintains a tubular structure, with many nanoparticles attached to the surface, and many holes appear on the surface. This is mainly due to the addition of iron salts and zinc salts during the preparation process. The iron salts are reduced to zero-valent iron particles during high-temperature carbonization, and the zinc salts play a pore-forming role. In addition, the addition of alkaline solution is another factor that causes the porous surface of the composite fiber. It can also be observed that the diameter of the zero-valent iron particles on the fiber surface is about 100nm, and they are evenly embedded in the surface and wall of the carbon fiber. In the figure, f is a cross-section of the hollow tube wall of the carbon-loaded iron-zinc-based composite material. It can be clearly observed that the tube wall of the composite expands under the synergistic effect of iron-zinc salts and alkali, and finally forms a multi-porous tube wall containing nano zero-valent iron. Its thickness is 2 times greater than that of the carbon fiber tube, about 800nm. This multi-porous structure allows the zero-valent iron particles to be better combined with the carbon fiber to form a heterojunction, which is more conducive to the transmission of electrons.
[0083] Figure 4This is the mapping diagram and EDS diagram of C / Fe / Zn-5. Figure 4 It can be clearly seen that C, O, Fe, and elements are evenly distributed on the carbon nanotube fibers. The C element mainly comes from the carbon fiber tube material, while the Fe element mainly comes from the zero-valent iron particles, and the O element mainly comes from the zero-valent iron oxide. This shows that the nano zero-valent iron particles are evenly loaded on the carbon nanotube fibers, which can effectively improve their photo-Fenton degradation effect. The atomic percentage of each element is shown in Figure f. The atomic ratio of C element in C / Fe / Zn-5 is 69.35%, the atomic ratio of O element is 26.86%, the atomic ratio of Fe element is 3.68%, and the atomic ratio of Zn element is 0.11%. Because the content of Zn element is too low, the Zn element is not effectively detected in Figure e.
[0084] Figure 5They are XRD spectra of C-1, C / Zn, C / Fe, C / Fe / Zn-5, etc. As shown in Figure a, the carbon fiber tube has two obvious broad diffraction peaks at 23° and 43°, which mainly correspond to the (002) and (100) crystal planes of the graphite structure, which is the amorphous structure of carbon, indicating that the sample obtained after carbonization of poplar fluff at 750°C is amorphous carbon with a certain graphite microcrystalline structure. When zinc metal salt is introduced into poplar fluff fiber, the XRD peak of the C / Zn composite obtained by carbonization has an obvious broad diffraction peak at 23°, and the characteristic peak at 43° disappears compared with Figure a, which is mainly attributed to the addition of zinc salt to create many holes on the carbon fiber tube wall, which reduces the degree of graphitization of carbon fiber to a certain extent. From Figure c and d, we can see that strong and sharp characteristic peaks appear at 44.7 and 65.2°, corresponding to the (110) and (200) crystal planes of the body-centered cubic structure α-Fe (JCPDS.No:06-0696), which proves that under high temperature conditions, iron ions are reduced by carbon to form zero-valent iron. In Figure c, obvious diffraction peaks appear at 30.1 and 35.5°, which are the diffraction peaks of the (220) and (311) crystal planes of Fe2O3 (JCPDS.No:39-1346). In Figure d, some small Fe2O3 diffraction peaks also appear at 30-40°, which may be due to incomplete reduction of iron ions during high-temperature carbonization or high activity of zero-valent iron, which is oxidized by oxygen in the air during storage. In addition, in Figures c and d, it can be clearly seen that the broad diffraction peak of amorphous carbon is almost invisible, and a clear new diffraction peak appears at 26.4°, which corresponds to the (002) crystal plane of the graphitized structure. This means that the C / Fe / Zn-5 composite material has initially formed a certain degree of graphitized structure at a carbonization temperature of 750°C, which is far lower than the graphitization temperature of carbon materials in the prior art (about 2000°C). This shows that the addition of Fe ions has a certain catalytic effect on the graphitization degree of carbon, and causes the amorphous carbon to transform to the aromatization stage, which improves the order of the carbon layer and causes the characteristic peak of graphitized carbon to appear at 26.4°. In summary, the addition of Fe ions not only causes the presence of highly active zero-valent iron in the composite material, but also improves the graphitization degree of carbon.
[0085] In order to further illustrate the application effect of the C / iron-based composite materials prepared in the above examples and comparative examples in photo-Fenton catalytic degradation, the following experiments were conducted.
[0086] 1. Drawing of the Rhodamine B standard curve
[0087] Weigh 1000 mg of RhB into a 500 mL beaker, add deionized water and stir with a glass rod until the RhB is completely dissolved. Then dilute the solution to a 1000 mL volumetric flask to prepare a concentration of 1000 mg·L -1RhB solution. According to relevant literature, the maximum absorption wavelength of RhB is 554nm. Use a 1000μL pipette to transfer 0μL, 50μL, 100μL, 150μL, 200μL, and 250μL of the prepared RhB solution to a 50mL volumetric flask, then add deionized water to the volume and shake well. The concentration of the RhB solution is 0mg·L -1 , 1mg·L -1 , 2mg·L -1 , 3mg·L -1 , 4mg·L -1 , 5mg·L -1 Using deionized water as the substrate, the absorbance of RhB solutions of different concentrations at 554 nm was measured using a UV-visible spectrophotometer. With C0 as the horizontal axis and absorbance (Abs) as the vertical axis, a standard curve of RhB solution was drawn, as shown in Figure 2. Figure 6 shown.
[0088] The standard curve equation of RhB solution obtained by linear fitting is:
[0089] y=0.19509x+0.00462(R 2 =0.9998)
[0090] From the above formula, we can see that the linear fit is very high. In the concentration range of 0 mg·L -1 -5mg·L -1 The values are in a linear relationship, where the abscissa x represents the concentration of the RhB solution and the ordinate y represents the absorbance.
[0091] 2. Photo-Fenton degradation experiment
[0092] Measure 200mg·L -150mL of RhB solution was placed in a 100mL double-layer jacket beaker, 0.05mL of concentrated HCL was added to adjust the pH of the solution to 2, and 20mg of any one of the C / iron-based composite materials prepared in Examples 1-5 was added, and placed in a visible light multiphase photocatalytic reactor, the light source was a 500W xenon lamp, and the temperature was maintained at 20°C using a water circulation system. After stirring with a magnetic stirrer for half an hour under dark conditions, the system reached adsorption-desorption equilibrium. 2mL of the suspension was taken with a 5mL syringe and filtered with a 0.45μm polyethersulfone filter membrane (PES), and its absorbance was measured with a UV-visible spectrophotometer. After that, 0.1mL of 30% H2O2 solution (32mM) was added to the RhB solution, and the visible light was turned on at the same time, and the photo-Fenton reaction was started under the xenon lamp light source. The suspension was taken at 1min, 2min, 3min, 4min, 5min, and 6min, filtered with 0.45μm PES, and the absorbance of the solution was measured at the maximum absorption wavelength of 554nm. The solution was substituted into the standard curve equation of RhB to calculate the remaining RhB concentration. The degradation catalytic effect of RhB is expressed by the removal rate η, and the calculation equation is as follows:
[0093]
[0094] Where C0 is the initial concentration of RhB solution, in mg·L -1 ; C t is the concentration of RhB solution at the end of the experiment, in mg·L -1 .
[0095] 3. Photo-Fenton degradation performance of C / Fe-based composites with different Zn-Fe doping amounts
[0096] like Figure 7 As shown in the figure, C-1 obtained by directly calcining poplar fluff at high temperature only shows a certain adsorption effect. When only NaOH (C-2) or only iron-zinc salt (C / Fe / Zn-8) is used in the synthesis system, its degradation rate is only slightly improved compared with C-1. When the two act together on poplar fluff fibers, the obtained sample has a higher degradation rate. It can also be seen from the figure that the degradation rates of C / Fe, C / Zn and Fe / Zn catalysts at 20 minutes are 99.6%, 23.4% and 34.5%, respectively, indicating that carbon and iron species play a key role in the composite material. In contrast, the degradation rate of C / Fe reaches 99% at 5 minutes, while that of C / Fe / Zn-5 reaches 99% at 2 minutes, indicating that zinc also has a certain synergistic effect in the composite material. In addition, with the increase of the amount of zinc salt and iron salt, the degradation rate of RhB first increased and then decreased. When the ratio of zinc salt to iron salt reached 1mmol:2mmol and 1.5mmol:1.5mmol, the catalytic degradation effect was the best, and both were within 2min for 200mg·L -1The degradation rate of RhB reached more than 99%. However, when the amount of zinc salt and iron salt reached 1.5mmol:3mmol, the degradation rate of RhB began to decrease, and the degradation rate was 89.3% at 5min of the photo-Fenton reaction. This phenomenon may be due to the excessive content of zinc salt, which caused the catalyst to agglomerate and affected the photo-Fenton activity. Therefore, the C / Fe / Zn-5 prepared in Example 3 had the best catalytic degradation effect.
[0097] 4. Effects of other factors on the performance of photo-Fenton degradation of RhB solution by Fe-Zn-based composite materials (refer to the experimental process of photo-Fenton degradation experiment)
[0098] (1) Photo-Fenton degradation of RhB by C / Fe-based composites at different pH values
[0099] Measure 200mg·L -1 50 mL of RhB solution was placed in a 100 mL double-layer jacketed beaker. The input amount of the C / iron-based composite material prepared in Example 3 was 0.4 g·L -1 , the amount of H2O2 was 32 mM, and the pH of the solution was 1, 2, and 3. The other steps were consistent with the photo-Fenton degradation experiment.
[0100] In the C / Fe-based composite material photo-Fenton catalytic degradation reaction system, different factors will have different effects on the photo-Fenton catalytic degradation of RhB solution by Fe-Zn-based composite materials. The research results on the effect of pH value on the experiment are as follows: Figure 8 As shown in the figure, in a solution with a pH value of 2, the 2-min removal rate of RhB is greater than 99% and can even reach 100%, while at pH values of 1 and 3, the 2-min removal rate of RhB is only 21% at most. This shows that although the applicable pH range of C / iron-based composite materials is relatively narrow, they have extremely high catalytic degradation activity within a specific pH range. At lower pH values, it may be due to the increase in the amount of iron ions dissolved in the solution, which increases the concentration of iron ions in the solution, which is conducive to reacting with H2O2 to generate rich H + to oxidatively degrade RhB. As the pH value increases, more and more OH — Will occupy Fe 3+ reaction sites, thus Fe 3+ The interaction between RhB and H2O2 will be reduced, resulting in a slower degradation efficiency of RhB by photo-Fenton. Therefore, the degradation effect is best when pH = 2.
[0101] (2) Photo-Fenton degradation of RhB by H2O2 on C / Fe-based composites
[0102] Measure 200mg·L -1 50 mL of RhB solution was placed in a 100 mL double-layer jacketed beaker. The input amount of the C / iron-based composite material prepared in Example 3 was 0.4 g·L-1 The pH of the solution was 2, and the amounts of H2O2 were 16 mM, 32 mM, and 48 mM, respectively. The other steps were consistent with the photo-Fenton degradation experiment.
[0103] In the C / iron-based composite material photo-Fenton catalytic degradation system, the catalyst reduction of H2O2 and the decomposition of H2O2 itself can produce hydroxyl radicals (·OH), so within a certain range, the amount of free radicals ·OH generated is proportional to the H2O2 concentration. The effect of H2O2 addition on the catalytic degradation efficiency of RhB solution is shown in Figure 2. Fig. 9 As shown. When the amount of H2O2 added increased from 16mM to 32mM, the removal rate of RhB increased from 87.0% to 95.7% at 1min, and the reaction rate was slightly accelerated. This shows that the H2O2 activated under light produced more free radicals ·OH, which directly accelerated the effect of the RhB degradation experiment. However, when the concentration of H2O2 increased again to 64mM, the degradation rate of RhB did not increase accordingly. This may be because the excessively high concentration of H2O2 captured ·OH, and then formed H2O and O2, thereby reducing the production of free radicals ·OH and did not increase the degradation effect on RhB. Therefore, when the content of H2O2 is 48mM, the degradation effect is best.
[0104] (3) Effect of catalyst dosage on photo-Fenton degradation of RhB in C / Fe-based composites
[0105] Measure 200mg·L -1 50 mL of RhB solution was placed in a 100 mL double-layer jacketed beaker. The pH of the solution was 2, the amount of H2O2 was 48 mM, and the input amounts of the C / iron-based composite material prepared in Example 3 were 0.3 g·L -1 , 0.4 g·L -1 , 0.5 g·L -1 The other steps were consistent with the photo-Fenton degradation experiment.
[0106] Effect of the dosage of C / Fe-based composite catalyst on the catalytic degradation of RhB Fig.10 As shown in the figure, when the amount of catalyst increases from 0.3 g·L -1 Increased to 0.4 g·L -1 , the degradation rate of RhB increased from 80.6% to 95.8% in 1 min. This is because the increase in the amount of catalyst provided more adsorption and catalytic active sites, so the experimental effect increased. When the amount of catalyst continued to increase to 0.5 g·L -1 The experimental results are similar, indicating that a higher concentration of catalyst will inhibit the rapid degradation of RhB by C / Fe-based composite materials. The reason for this phenomenon may be that when the mass of C / Fe-based composite catalyst is small, the photogenerated electron-hole (h+ ) is produced in small amounts, so the catalytic degradation performance is not high. As the amount of catalyst increases, h + The number of photo-Fenton will also increase, and the photo-Fenton performance will gradually improve. + At this point, increasing the amount of catalyst will not only fail to improve the efficiency of photo-Fenton, but too much catalyst will block the contact area between light and pollutants in the solution, which will affect the photo-generated + The generation of photo-Fenton efficiency is reduced. Therefore, the catalyst dosage is 0.4 g·L -1 The degradation effect is best.
[0107] 5. Fourier Transform Infrared Spectroscopy (FT-IR)
[0108] like Fig.11 As shown, the fiber diameters of poplar fluff are 3400, 2910, 1741, 1609, 1387, 1240, and 1051 cm -1 A strong absorption peak appeared at 3400 cm -1 The nearby peak is attributed to -OH stretching vibration; 2910cm -1 The stretching vibration peak of the CH bond in -CH2 is 1741cm -1 The stretching vibration peaks of C=O are at 1609, 1387 cm -1 The peak belongs to the C=O axial vibration peak; 1240cm -1 It is the CO bending vibration peak of esters and phenols in poplar fluff; 1055cm -1 It is the CO stretching vibration peak in poplar cellulose. As shown in Figure b, after high-temperature carbonization, its peak at 3400cm -1 The -OH stretching vibration peaks near 1608 and 1110 cm -1 Weaker C=O and CO broad peaks are seen near 1740-1051cm -1 Obvious C=O and CO characteristic absorption can be seen at 1440, 875cm -1 A new strong absorption peak appeared at 623 cm, corresponding to the C-OH and CH stretching vibration peaks, which means that the addition of iron salts improves the carbonization degree of carbon materials. -1 There is an obvious Fe-OH absorption peak at , which further proves that iron is successfully loaded on the carbon fiber.
[0109] 6. Specific surface area and pore size analysis
[0110] like Fig.12As shown in Table 2, the C / iron-based composite materials prepared in the examples and comparative examples were subjected to nitrogen adsorption and desorption tests, from which it can be seen that the specific surface area of the poplar fluff without any treatment is about 36.440 m 2 / g, pore volume 0.065cm 3 / g. After carbonization at 750℃, the adsorption-desorption curve showed an obvious hysteresis loop, which proved that the obtained carbon fiber material was a porous material, and its specific surface area increased to 86.329m 2 / g, pore volume reaches 0.150cm 3 / g, which is more than twice that of poplar fluff. When the porogen zinc salt is added to the poplar fluff fiber, the C / Zn specific surface area is significantly increased to about 102.067m 2 / g, which confirms that the introduction of zinc salt does play a pore-forming role and thus increases the specific surface area. When only Fe salt is added to poplar fibers, the C / Fe specific surface area is reduced to 37.078m 2 / g, which may be because Fe nanoparticles grow on the carbon fiber wall, blocking the original pores of carbon and reducing the specific surface area. Compared with C / Fe, the specific surface area of C / Fe / Zn-5 is increased, and the pore volume is increased from 0.092cm 3 / g increased significantly to 0.152cm 3 / g, which may be caused by the synergistic effect of iron and zinc salts, which proves that zero-valent iron nanoparticles are successfully loaded on the carbon fiber tube wall.
[0111] Table 2 Physical properties of different samples
[0112]
[0113] 7. Three-dimensional fluorescence detection
[0114] Fig.13 The C / iron-based composite material prepared in Example 3 is shown to detect the degradation process of RhB using three-dimensional fluorescence technology. As shown in Figure A, the peak a at 560-610 / 595-650nm and the peak b at 310-470 / 595-660nm are two fluorescence characteristic peaks of RhB. As the dark reaction proceeds, after 30min (Figure B), the peak a, peak b and peak c centers do not move significantly, indicating that the adsorption effect of the catalyst is general. In addition, as the photo-Fenton reaction ends at 6min, peak a and peak b disappear (Figure C), indicating that the RhB molecules have been completely decomposed into small inorganic salt molecules.
[0115] 8. Photo-Fenton cycle test of C / iron-based composites
[0116] The fixed experimental reaction conditions are: the input amount of the C / iron-based composite material prepared in Example 3 is 0.4 g·L -1The pH of the solution was 2, the amount of H2O2 was 36 mM, and according to the above-mentioned experimental method of photo-Fenton catalysis, the supernatant was not taken in the middle. After the reaction was completed, the solution was poured into a beaker, and the remaining catalyst was adsorbed to the bottom wall of the beaker with a magnet. The upper clear liquid was poured out, and the remaining C / iron-based composite material raw material was washed three times with deionized water, and then 200 mg·L of the same concentration was added again. -1 50 mL of RhB solution was added and the next catalytic degradation experiment was started. The same experimental steps were repeated 5 times.
[0117] like Fig.14 As shown in the figure, the catalytic degradation efficiency of C / Fe-based composite catalyst for RhB can still be as high as 99% after repeated cycles for 5 times. In addition, since C / Fe-based composite catalyst is magnetic, it can be more easily separated and recovered from the solution through an external magnetic field, so as to be further recycled, which is particularly important for the practical use of composite catalysts.
[0118] 9. Magnetic performance test
[0119] like Fig.15 As shown in the figure, the C / iron-based composite materials prepared by different systems are all black flocculent fibers, which can move in a directional manner under an external magnetic field. The black flocculent fibers are tightly adsorbed on the side wall by the magnet, which proves that the prepared C / iron-based composite materials have strong magnetic response properties. This feature is conducive to the recycling of experimental materials in degraded wastewater, greatly improving their recycling value.
[0120] 10. Photo-Fenton degradation mechanism
[0121] Measure 200mg·L -1 50 mL of RhB solution was placed in a 100 mL double-layer jacketed beaker. The pH of the solution was 2, the amount of H2O2 was 36 mM, and the amount of C / iron-based composite material prepared in Example 3 was 0.4 g·L -1 , and 0.5mmol isopropanol (IPA), 0.5mmol triethanolamine (TEA), and 0.05mmol p-benzoquinone (BQ) were added as ·OH, h + 、O2 — capture agent.
[0122] In the experiment, isopropyl alcohol (IPA), triethanolamine (TEA), and p-benzoquinone (BQ) were used as the capture agents for hydroxyl radicals (·OH) and photogenerated holes (h + ), superoxide radicals (·O2 — ) capture agent, such as Fig.16The figure shows the effect of different scavengers on the photo-Fenton catalytic degradation efficiency of RhB. After 2 minutes of reaction, the photo-Fenton catalytic degradation rate of RhB by C / Fe-based composite material without adding scavenger was 99.8%; after adding triethanolamine (TEA), the photo-Fenton catalytic degradation rate of RhB dropped sharply to 8.7%, which indicates that triethanolamine (TEA) captures photogenerated holes (h + ) free radicals, which significantly reduced the degradation ability of the catalyst, and also proved that the photogenerated holes (h + ) plays a major role in the photo-Fenton catalytic degradation of RhB. When isopropyl alcohol (IPA) and para-benzoquinone (BQ) were added, the photo-Fenton catalytic degradation rates of RhB decreased to 75.3% and 98.3%, respectively. Among them, the catalytic degradation effect was significantly weakened after adding isopropyl alcohol (IPA), while the degradation effect was not significantly weakened after adding para-benzoquinone (BQ). These results show that in the experimental reaction system of photo-Fenton catalytic degradation of RhB by C / Fe-based composite materials, photogenerated holes (h + ) and hydroxyl radicals (·OH) are the active species in the photo-Fenton catalytic degradation experiment of C / Fe-based composites.
[0123] In summary, when poplar fibers are modified by iron salt, zinc salt and NaOH together, the C / iron-based composite material prepared in Example 3 is based on the addition of 50 mL of anhydrous ethanol and 0.5 g of pure poplar fibers. When the zinc-iron molar ratio is 1.5 mmol: 1.5 mmol and the C / Fe / Zn-5 catalyst obtained by calcining under an argon atmosphere has the best degradation rate, and its degradation rate of 200 mg·L-1RhB reaches more than 99% in 2 min.
[0124] At 200 mg·L -1 RhB was the target pollutant, and the effects of different pH, different H2O2 concentrations, and different amounts of catalyst on the photo-Fenton degradation ability of C / iron-based composite materials were explored. The results showed that the optimal conditions for the degradation experiment were: pH = 2, H2O2 dosage of 36mM, and catalyst dosage of 0.4g·L -1 .
[0125] In addition, the C iron-based composite material based on willow catkin fibers prepared in Example 6 has the same performance as the C iron-based composite material based on poplar catkin fibers, and both can be used in photo-Fenton catalytic degradation.
[0126] The above are only preferred embodiments of the present invention and the technical principles used. Those skilled in the art will understand that the present invention is not limited to the specific embodiments described herein, and that various obvious changes, readjustments and substitutions can be made by those skilled in the art without departing from the scope of protection of the present invention. Therefore, although the present invention is described in more detail through the above embodiments, the present invention is not limited to the above embodiments, and may include more other equivalent embodiments without departing from the concept of the present invention, and the scope of the present invention is determined by the scope of the appended claims.
Claims
1. A method for preparing a C / iron-based composite material based on poplar / willow catkin fibers, characterized in that: The following steps are involved: Collect poplar / willow catkins, wash and dry them to obtain pure poplar / willow catkins; Dissolving a divalent zinc salt and a trivalent iron salt in a solvent to obtain a mixed solution; Put pure poplar / willow catkins into the mixed solution and stir, adjust the pH to alkaline, and obtain a suspension; The suspension is washed, filtered, dried and calcined to obtain a C / iron-based composite material.
2. The method for preparing a C / iron-based composite material based on poplar / willow catkin fibers according to claim 1, characterized in that: In the mixed solution, the concentration of the divalent zinc salt is 20mmol / L-40mmol / L, and the molar ratio of the divalent zinc salt to the trivalent iron salt is 1:(1-2); in the suspension, the concentration of pure poplar / willow catkins is 8g / L-12g / L 。 3. The method for preparing a C / iron-based composite material based on poplar / willow catkin fibers according to claim 1, characterized in that: The divalent zinc salt includes zinc nitrate hexahydrate, the trivalent iron salt includes ferric nitrate nonahydrate, and the solvent includes anhydrous ethanol.
4. The method for preparing a C / iron-based composite material based on poplar / willow catkin fibers according to claim 1, characterized in that: The drying temperature of the poplar / willow catkins is 50-70°C.
5. The method for preparing a C / iron-based composite material based on poplar / willow catkin fibers according to claim 1, characterized in that: The pure poplar / willow catkins are placed in the mixed solution and stirred for 10-60 minutes.
6. The method for preparing a C / iron-based composite material based on poplar / willow catkin fibers according to claim 1, characterized in that: The pH is adjusted to alkaline, with a pH value of 9-10.
7. The method for preparing a C / iron-based composite material based on poplar / willow catkin fibers according to claim 1, characterized in that: The drying temperature of the suspension is 50-80° C.; the calcination temperature is 600-800° C., and an inert atmosphere is maintained during the calcination process.
8. A C / iron-based composite material based on poplar / willow catkin fibers, characterized in that: It is prepared by the preparation method described in any one of claims 1 to 7.
9. A photo-Fenton catalyst, characterized in that: Comprising the C / iron-based composite material as described in claim 8.
10. The catalytic method of photo-Fenton catalyst according to claim 9, characterized in that: Photo-Fenton degradation was carried out under the conditions of different Fe-Zn doping amounts, different synthesis systems in alcohol phase or water phase, and different calcination methods in air or argon.